Digging Out and Filling In: Making Land on the Toronto Waterfront in the 1850s - McIlwraith, Thomas (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1991)
A half-million square metres (50 hectares) was brought in to railroad and commercial use at wharfage-level along the Toronto lakefront during the 1850s. This major engineering project involved cutting down the terrace south of Front Street, and this was the source of most of the fill dumped into the Bay. Neither railroad cars nor harbour dredges were capable of delivering the additional material necessary for building anticipated port lands, and many parts of the waterfront remained improperly filled for decades. The land-area that was created should be regarded as a byproduct of short-run, selfish commercial interests, abetted by a City Council that gave only lip-service to the concept of a parklike lakefront.